Trends in Integrated Islamic Schools in Rural Areas: Background and Parent's Orientation in Choosing SDIT as an Alternative to Elementary Schools in Boyolali - Sumadi, Eko; Sutrisno, Sutrisno; Ro'fah, Ro'fah (Program Studi Pendidikan Agama Islam, 2021)
AbstractThis study aimed to explain the trend shifting of elementary schools in the Boyolali District. Some of the questions that would be answered through this research were: 1) Why did SDIT become a trend in rural areas? 2) What were the motives and orientations of parents in choosing SDIT as an alternative primary school for their children? The study of this theme was conducted using a qualitative research approach. Data were collected through observation techniques, in-depth interviews, and document analysis. The data obtained were then processed and analyzed in six stages: transcribing the interview data, labeling all the data obtained, categorizing the data into cognate themes, narrating the data by comparing and contrasting, interpreting the data, and finally drawing conclusions. The results of this study found two main conclusions: 1) The development of SDIT trends in Boyolali was directly proportional to the increasing of the religious awareness of the community, which was driven by the massive development of socio-religious foundations representing various theological concepts, where the foundations felt that they needed to establish Islamic schools as media to regenerate and maintain the continuity of their respective theological concepts. 2) Beside that, not only the theological and academic factors (quality of education), but also the economic and the children's independence factors were the motives and orientations of parents in determining the choice of primary school for their children.